Lymphocyte transformation in patients with paraproteinaemia - Campbell, A E; De Vine, J; Azam, L; Hamid, J; Delamore, I W; McFarlane, H (British journal of haematology, 1975)
The transformation of lymphocytes in cultures with phytohaemagglutinin (PHA) or with pokeweed mitogen (PWM) was carried out during treatment on 28 patients with paraproteinaemia and on 20 control subjects. 78.5% of the peripheral blood lymphocyte short-term cultures from the treated patients showed a subnormal PHA-induced but high PWM-induced lymphocyte transformation. The other 21.5% of the treated patients had a normal pattern of lymphocyte transformation. Eight of 12 untreated patients with multiple myelomatosis and four of five untreated patients with benign paraproteinaemia also had a subnormal lymphocyte transformation to PHA but a high response to PWM. Serial lymphocyte transformation studies in eight of 18 myeloma patients during chemotherapy revealed that the initial subnormal lymphocyte transformation to PHA subsequently became higher than that to PWM. 82% of the bone marrow cultures from the patients showed a higher PWM-induced than PHA-induced lymphocyte response, also suggesting a B cell type of disease. In both dose response and time dependent investigations peak transformation of peripheral blood lymphocytes did not always coincide.